The Obstacles of Labor Inspection in Protecting Workers’ Rights in Indonesia - SANTOSO, Budi (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Labor inspection system is the fundamental function of labor law enforcement and effective compliance. Nevertheless, the lack of the system contributes to difficulties in promoting labor law compliance. This article aims to analyze the obstacles of labor inspection in Indonesia during the function be conducted by the district/regency government. By using descriptive and analytical methods, it can be concluded that there are some obstacles faced by the labor inspectors in the district/regency level in order to protect the workers’ rights. Those are the labor inspection planning is not going well, the stages of labor inspection process are not enforced, the number of labor inspector is not comparable with the number of companies that must be inspected, some the district/regency employment offices does not have civil servant investigators, intervention by local officials, no rotation of work area of the labor inspectors, most companies are small enterprises, and overlapping duties between labor Inspectors and mediators on advisory duty. These obstacles have caused the rights of workers to be less protected.